EFFECT OF AQUEOUS PLANT EXTRACTS AND INORGANIC FERTILIZER ON THE GERMINATION, GROWTH AND DEVELOPMENT OF MAIZE (Zea mays) (FUDMA JOURNAL OF SCIENCES, 2023)
This study was conducted to evaluate the effect of Plant extract and inorganic fertilizer on the germination and early seedling growth of maize, Bio-fertilizers have the ability to symbiotically relate to the roots of plants. These living microorganisms help to transform complicated organic material into basic compound, helping the plant to grow and nurture in a natural way.  Aqueous extracts of Azadirachta indica was obtained using cold maceration method the experiment was designed in  a completely randomize design both in the  in vitro and field experiments, the germination rate, plumule and radicle lengths as well as the dry matter accumulations of the maize plant were determined. The extract was diluted using serial dilution method to obtain 100,75,50, & 25% of the extract and an inorganic fertilizer NPK. Aqueous extract of the plant  demonstrated ability to stimulate the germination, growth and development of maize crop. The effect of the extracts increases with increase in the concentration of the extracts with the best activity in 100% concentration of the extract, which was as effective as the Inorganic fertilizer in all the parameters considered used in the studies. Application of organic biofertilizer is recommended as it increases the yield and early germination of the plant.
Keywords: Fertilizer; Azadirachta indica; Germination; Maize